Analysis of Engineering and Geological Conditions of International Submarine Optical Fiber Cable Routing in the East China Sea Section. (28th June 2022) - Zhang, Ti-qiang; Fan, Zi-xian; Ning, Nan; Tang, Jian-zhong; Kou, Dai-xin
Abstract : The East China Sea section of the Chinese international submarine optical fiber cable generally starts from the Shanghai coast, crosses the East China Sea shelf and continental slope to the east, and intersects with the international optical fiber cable system in Okinawa Trough. In this paper, the regional tectonic, seismic, and other environmental conditions of the East China Sea section of the international submarine optical cable are briefly described based on the previous data. Additionally, the geological engineering conditions of the international optical cable routing in the East China Sea area will be analyzed based on the field investigation data such as multibeam, side-scan sonar, shallow stratigraphic profile, sediment sampling, and cone penetration test (CPT). It is found that the main geological factors in the East China Sea shelf area are submarine scouring, sandwave, shallow gas, and hard seabed; in the land slope area are steep slope, submarine valley, rock, landslide, and shallow gas (pockmark); and in the Okinawa Trough area are gully, sea mound/seamount, rock, shallow gas, fault, and hard strata outcrop. This paper briefly analyzes the impact of each geological disaster factor on the submarine cable project and proposes solutions for providing essential information and some scientific basis for designing, constructing, operating, and maintaining international submarine optical fiber cables in the East China Sea area.